Explicație pas cu pas:
ax + b = 0
a) a = 1 și b = 4
[tex]\implies \bf x + 4 = 0[/tex]
b) a = -3 și b = -2
[tex]\implies \bf -3x -2 = 0[/tex]
c) a = 1,5 și b = -1
[tex] \frac{3}{2}x - 1 = 0 \implies \bf 3x - 2 = 0 \\ [/tex]
d) a = 0,(5) și b = 2,5
[tex] \frac{5}{9}x + \frac{5}{2} = 0 \iff 10x + 45 = 0 \\ \implies \bf 2x + 9 = 0[/tex]
e) a = 2/5 și b = 3/4
[tex] \frac{2}{5}x + \frac{3}{4} = 0 \implies \bf 8x + 15 = 0 \\ [/tex]
f) a = √7 și b = -2√6
[tex]\implies \bf \sqrt{7}x - 2 \sqrt{6} = 0[/tex]